ANALISIS FRAMING PEMBERITAAN TERHADAP KONTROVERSI IJAZAH PRESIDEN JOKO WIDODO: STUDI KOMPARASI MEDIA TEMPO DAN KOMPAS: A Comparative Study of Tempo and Kompas Media - uddin, syarif (representamen, 2025)
The media is a mouthpiece for the general public to get important information related to politics, government issues, and issues concerning state officials. As well as government ownership documents. This research seeks to explain the controversial case of Joko Widodo's diploma, which was previously claimed to be fake by several parties. This study aims to determine the framing done by Tempo and Kompas journalists on the news of demonstrations about Jokowi's diploma. This research method uses a narrative qualitative method, a literature study approach. The data collection technique uses library research techniques, collecting data from books, journals and literatures. The results of this study show that the framing of Tempo journalists is more procedural and neutral in reporting the demonstration of Jokowi's diploma case. While the framing done by Kompas journalists tends to be more emotional, revealing the feelings or disappointment of the demonstrators towards the case. Keywords: framing analysis, presidential diploma, news coverage